Clinical Consensus Statement: Ankyloglossia in Children. (14th April 2020) - Messner, Anna H.; Walsh, Jonathan; Rosenfeld, Richard M.; Schwartz, Seth R.; Ishman, Stacey L.; Baldassari, Cristina; Brietzke, Scott E.; Darrow, David H.; Goldstein, Nira; Levi, Jessica; Meyer, Anna K.; Parikh, Sanjay; et al.
Abstract : Objective: To identify and seek consensus on issues and controversies related to ankyloglossia and upper lip tie in children by using established methodology for American Academy of Otolaryngology–Head and Neck Surgery clinical consensus statements. Methods: An expert panel of pediatric otolaryngologists was assembled with nominated representatives of otolaryngology organizations. The target population was children aged 0 to 18 years, including breastfeeding infants. A modified Delphi method was used to distill expert opinion into clinical statements that met a standardized definition of consensus, per established methodology published by the American Academy of Otolaryngology–Head and Neck Surgery. Results: After 3 iterative Delphi method surveys of 89 total statements, 41 met the predefined criteria for consensus, 17 were near consensus, and 28 did not reach consensus. The clinical statements were grouped into several categories for the purposes of presentation and discussion: ankyloglossia (general), buccal tie, ankyloglossia and sleep apnea, ankyloglossia and breastfeeding, frenotomy indications and informed consent, frenotomy procedure, ankyloglossia in older children, and maxillary labial frenulum. Conclusion: This expert panel reached consensus on several statements that clarify the diagnosis, management, and treatment of ankyloglossia in children 0 to 18 years of age. Lack of consensus on other statements likely reflects knowledge gaps and lack of evidence regarding the diagnosis, management, and treatment of ankyloglossia. Expert panel consensus may provide helpful information for otolaryngologists treating patients with ankyloglossia.